Microencapsulation and in situ incubation methodology for the cultivation of marine bacteria - Pope, Emily; Cartmell, Christopher; Haltli, Bradley; Ahmadi, Ali; Kerr, Russell G. (Frontiers in Microbiology, 2022)
Environmental microorganisms are important sources of biotechnology innovations; however, the discovery process is hampered by the inability to culture the overwhelming majority of microbes. To drive the discovery of new biotechnology products from previously unculturable microbes, several methods such as modification of media composition, incubation conditions, single-cell isolation, and in-situ incubation, have been employed to improve microbial recovery from environmental samples. To further improve microbial recovery, this study examined the effect of microencapsulation followed by in-situ incubation on the abundance, viability and diversity of bacteria recovered from marine sediment samples. Bacteria from marine sediment samples were resuspended or encapsulated in agarose and half of each sample was directly plated on agar and the other half inserted into modified commercially available Slyde-A-LyzerTM dialysis cassette diffusion chambers. The diffusion chambers were incubated in their natural environment (in-situ) for a week, after which they were retrieved, and the contents plated on agar. Colony counts indicated that bacterial abundance increased during in-situ incubation and that overall cell density was significantly higher in cassettes containing non-encapsulated sediment bacteria. Assessment of viability using a Live/Dead assay indicated that a higher proportion of cells in encapsulated samples were viable at the end of the incubation period, suggesting that agarose encapsulation promoted higher cell viability during in-situ incubation. One hundred and forty-six isolates were purified from the study (32-38 from each treatment) to assess the effect of the four treatments on cultivable bacterial diversity. In total, 58 operational taxonomic units (OTUs) were identified using a 99% 16S rRNA gene sequence identity threshold. The results indicated that encapsulation recovered greater bacterial diversity from the sediment than simple resuspension (41 vs. 31 OTUs, respectively). Interestingly, while the cultivable bacterial diversity decreased by 43-48% after in-situ incubation, difficult to culture (Verrucomicrobia) and obligate marine (Pseudoalteromonas) taxa were only recovered after in-situ incubation. These results suggest that agarose encapsulation coupled with in-situ incubation in commercially available, low cost, diffusion chambers facilitate the cultivation and improved recovery of bacteria from marine sediments. This study provides another tool that microbiologists can use to access microbial dark matter for environmental studies and biotechnology bioprospecting.